OPS Effect of the Use of Audio Visual Media on the Learning Outcomes of Class IV Students at Negeri 091299 Sipoldas - Simanjuntak, Tika Plorentina; Sijabat, Osco Parmonangan; Sijabat, Desi (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2022)
This study aims to determine the effect of using audio-visual media on the learning outcomes of fourth grade students at SD Negeri 091299 Sipoldas. In this study, the researcher used quantitative research with a pre-experimental design in the form of one group pre-test post-test design. The population in this study were all fourth grade students of SD Negeri 091299 Sipoldas. The sample in this study amounted to 27 students. The sampling technique in this study is a saturated sampling technique. Data collection techniques in this study are documentation and tests (pre-test post-test). The data analysis technique used is descriptive statistical test, normality and homogeneity. This data was analyzed with the help of Windows SPSS 21. The hypothesis testing of this study used the calculation of the independent sample T-Test test. The results showed that the tcount value was 8.930 ttable 2.052, so Ha was accepted and Ho was rejected. It can be concluded that the hypothesis of this research is accepted, namely that there is an effect of using audio-visual media on student learning outcomes in sub-theme 1 types of work in class IV SD Negeri 091299 Sipoldas.